Supporting Factors in The Development of Muslim Friendly Tourism in Palembang City - Tri Yuniningsih; Ida Hayu Dwimawanti; Dyah Lituhayu (Universitas Medan Area, 2023)
Tourism is a very strategic sector in implementing the sustainable development goals. In addition, tourism is also the main contributor to foreign exchange income in developing countries. Tourism in the international scope has experienced various development trends, one of which is halal tourism which is known as Muslim-friendly tourism. Muslim-friendly tourism is a stage of tourism by providing basic necessities needed by a Muslim tourist in accordance with applicable Islamic law. In Indonesia, Muslim-friendly tourism has begun to develop, one of which is in the city of Palembang which is a leading tourist destination in South Sumatra Province which can be used as an opportunity to develop Muslim-friendly tourism. This research focuses on the development of Muslim-friendly tourism in Palembang City. In order to approach this problem, a reference to the theory of supporting factors in tourism development is used. The data were collected through interviews, documentation, FGDs and analyzed qualitatively. This study concluded that the factors that influence the development of Muslim tourism in Palembang City are the values underlying cooperation between actors, the patterns and communication media used to communicate between actors, the level of trust of actors in cooperation, the implementation of cooperation policies between actors, and other factors.